Genetic algorithm application for traffic light control - Turky A.M.; Ahmad M.S.; Yusoff M.Z.M.; Sabar N.R. (Springer Verlag, 2023)
In this paper, we describe the design of an intelligent traffic light control based on genetic algorithm. This paper is part of our work in which we attempt to use genetic algorithm in traffic light control and pedestrian crossing. In our approach, we use four sensors; each sensor calculates the vehicle density for each lane. We developed an algorithm to simulate the situation of an isolated intersection (four lanes) based on this technology. We then compare the performance between the genetic algorithm controller and a conventional fixed time controller. 2009 Springer Berlin Heidelberg.